صعوبات التعلم النمائية (الانتباه، الإدراك، الذاكرة) في المدارس الابتدائية من وجهة نظر أساتذة التعليم الابتدائي -دراسة ميدانية في بعض ابتدائيات مدينة المسيلة- - عريوة هجيرة; موساوي فيروز; اشراف: جعلاب نور الدين (جامعة محمد بوضياف -المسيلة, 2025)
هدفت الدراسة إلى الكشف عن مؤشرات صعوبات التعلم النمائية (الانتباه، الإدراك، الذاكرة) في المدارس الابتدائية من وجهة نظر أساتذة التعليم الابتدائي-دراسة ميداينة في بعض ابتدائيات مدينة المسيلة-، وقد وُظِفَ المنهج الوصفي التحليلي في مجريات الدراسة، حيث تم اختيار عينة عشوائية قدرت ب (70) أستاذا وأستاذة، وطبق عليهم مقياس جاهز من إعداد عادل عبد الله محمد(2006) بغرض جمع البيانات لاستخدامها في التحقق من صحة الفرضيات مستخدمين الاساليب الإحصائية التالية: (المتوسطات الحسابية، الانحرافات المعيارية ، التكرارات) وتوصلت الدراسة إلى نتيجة عامة مفادها أن: - مستوى مؤشرات صعوبات التعلم النمائية لدى تلاميذ التعليم الابتدائي ''مرتفع'' من وجهة نظر أستاذة التعليم الإبتدائي. كما توصلت الدراسة إلى نتائج جزئية جاءت كما يلي: - مستوى مؤشرات صعوبات الانتباه لدى تلاميذ التعليم الابتدائي ''مرتفع'' من وجهة نظر أستاذة التعليم الإبتدائي. - مستوى مؤشرات صعوبات الإدراك لدى تلاميذ التعليم الابتدائي ''مرتفع'' من وجهة نظر أستاذة التعليم الإبتدائي. - مستوى مؤشرات صعوبات الذاكرة لدى تلاميذ التعليم الابتدائي ''مرتفع''من وجهة نظر أستاذة التعليم الإبتدائي. الكلمات المفتاحية: صعوبات التعلم النمائية، صعوبات الانتباه، صعوبات الإدراك، صعوبات الذاكرة Abstract The study aimed to explore the indicators of learning difficulties (attention, perception, and memory) in primary schools from the perspective of elementary school teachers – a field study conducted in selected primary schools in the city of M'sila. The descriptive-analytical method was employed in the course of the study. A random sample of 70 male and female teachers was selected, and data were collected using a standardized scale developed by Adel Abdallah Mohamed (2006). The data were used to test the research hypotheses using the following statistical methods: means, standard deviations, and frequencies. The general finding of the study indicated that: • The level of developmental learning difficulty indicators among primary school pupils is considered "high" from the perspective of elementary school teachers. The study also revealed the following specific results: • The level of attention difficulty indicators among primary school pupils is "high" from the perspective of elementary school teachers. • The level of perception difficulty indicators among primary school pupils is "high" from the perspective of elementary school teachers. • The level of memory difficulty indicators among primary school pupils is "high" from the perspective of elementary school teachers. Keywords: developmental learning difficulties, attention difficulties, perception difficulties, memory difficulties.